2006
DOI: 10.1002/ptr.1836
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition activities of natural products on serine proteases

Abstract: Proteases play a key role in a variety of pathologies, including cancer, pancreatitis and thrombosis. Low molecular inhibitors can act as drugs to combat these pathologies. Twelve natural phenolic compounds and one alkaloid were evaluated. Quercetin was used as a standard in the in vitro tests on serine proteases (trypsin, thrombin and urokinase). Salicin showed a highly selective effect with a value of IC50 = 11.4 microm for thrombin, suggesting it may be a suitable lead structure for developing thrombin inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 9 publications
2
34
0
1
Order By: Relevance
“…Strategies to search for natural compounds based on ethno-botanical and chemo-taxonomical studies were described (Basso et al 2005). The present work followed also the previous study on inhibition activities of limited number of phenolic compounds toward serine proteases (Jedinák et al 2006).…”
Section: Resultsmentioning
confidence: 78%
“…Strategies to search for natural compounds based on ethno-botanical and chemo-taxonomical studies were described (Basso et al 2005). The present work followed also the previous study on inhibition activities of limited number of phenolic compounds toward serine proteases (Jedinák et al 2006).…”
Section: Resultsmentioning
confidence: 78%
“…2,21,22 Moreover, quercetin has been shown to inhibit amylase release induced by agonists such as cholecystokinin, carbachol, phorbol ester tetra decanoylphorbol-13--acetate. [23][24][25] A recent study has shown that one hour after the last dose of cerulein administration, quercetin treatment attenuates the development of AP in mice. The aim of the present study was to evaluate the protective and therapeutic effects of quercetin on pancreatic injury in cerulein-induced acute pancreatitis in rats.…”
Section: Methodsmentioning
confidence: 99%
“…var, major recorded in the Chinese Pharmacopoeia, 1) mainly contain hyperoside (HP), a ‰avonol glycoside, whose quality is controlled via determining HP using highperformance liquid chromatographic (HPLC) method. Thereby, many researches about HP appeared in literature, such as, the treatment of antidepressant, 2) cancer therapy, 3) strong inhibitor of HBsAg and HBeAg secretion in 2.2.15 cells and DHBV-DNA levels in the HBV-infected duck model, 4) possessing cytoprotective properties against oxidative stress by scavenging intracellular ROS and enhancing antioxidant enzyme activity, 5) protecting against the oxidative damage induced by TBHP, 6) and remarkable wound healing and anti-in‰ammatory. 7) Otherwise, many methods including capillary zone electrophoresis with electrochemical detection, 8) HPLC 9 11) and LC-MS/MS 12) have been reported for quantiˆcation of HP in various herbal medicines and biological ‰uids.…”
Section: Introductionmentioning
confidence: 99%